EVALUASI TRANSISI PEMBELAJARAN DIGITAL: STUDI KUALITATIF TENTANG DESAIN, PROSEDUR, DAN PELAKSANAANNYA: Bahasa Indonesia - Ali Rosad; Hernani; Didi Sudarmansyah; Rabiyatul Adawiyah Siregar; Handoko (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to analyse the evaluation of the digital transformation policy for learning at SMKN 2 Metro, covering the design, procedures and implementation of technology-based educational policies. The study employs a qualitative approach using the case study method. Data collection was carried out through observation, interviews and documentation, whilst data analysis was conducted through data reduction, data presentation and drawing conclusions using triangulation techniques. Unlike previous studies, which generally focused on the implementation of learning technologies or teachers’ digital competences, this study fills a gap by comprehensively evaluating digital transformation policies using the CIPP Model to analyse the design, procedures and implementation of policies at vocational secondary schools. The research findings indicate that the digital transformation of learning at SMKN 2 Metro has been implemented through the use of a Learning Management System (LMS), digital learning resources, and the adoption of hybrid learning as a form of educational adaptation. However, challenges remain, including the uneven level of teachers’ digital competence, limitations in technological infrastructure, the quality of the internet connection, and policy evaluation that remains predominantly administrative in nature. Analysis using the CIPP model indicates that the implementation of digital transformation has progressed reasonably well in terms of context, input, process and product, although there is still a need to strengthen technology-based learning evaluation. The Connectivism perspective suggests that learning is evolving towards a system based on digital connectivity and student-centred learning. The research findings confirm that the success of digital transformation in education is determined not only by the use of technology, but also by the readiness of human resources, the organisational culture of schools, and the effectiveness of continuous evaluation of educational policies